PUENTE DE LOS ASNOS: UNA PROPUESTA DE APLICACIÓN PARA LA ENSEÑANZA. - Gómez Álvarez, José Enrique (Andamios)
It is presented a new simplified version the procedure called Pons asinorum (the bridge of the asses) using classical sources and rearrangement Hamblin´s (1976) proposal. The article provides a brief description of the Pons asinorum sense and describes in brief other attempts at syllogism automatization. In a second moment compares the texts of John of Saint Thomas and Aristotle to show the theoretical steps taken for the software development. The third section the paper proposes a software application for the purpose of teaching, which represents an enhanced version of the logical device by introducing technical and conceptual improvements that render useful logical applications. The paper shows why this type of software can be a new form to teach classical themes in Logic with new ways.